Redesigning a Product Using Modern CAD-CAM Software. (2015) - Andrei, Adam; Cristian, Cosma; Alexandru, Comsa; Adrian, Pop
Abstract: After products are on the market for some time, they often need to be redesigned to meet new market requirements. New products are generally derived from similar but outdated products. Redesigning a product is an important part of the production and development process. The purpose of this paper is to show that using modern technology, like Digital Prototyping in industry is an effective way to produce new products. This paper tries to demonstrate and highlight the effectiveness of the concept of Digital Prototyping, both to reduce design time of a new product, but also the costs required for implementing this step. This paper presents a set of stages that focused on the particular processing conditions of redesigning a product. The paper follows all stages of research and production, from analyzing the existing product, creating a 3D model of the product, adding new features and testing the new product.